Differential processing of CRISPR RNA by LinCas5c and LinCas6 of Leptospira - Anand, Vineet; Prabhakaran, Harshini Sheeja; Prakash, Aman; Hussain, Md Saddam; Kumar, Manish (Biochimica et biophysica acta. General subjects, 2023)
Leptospira interrogans serovar Copenhageni's genome harbors two CRISPR-Cas systems belonging to subtypes I-B and I-C. However, in L. interrogans, the subtype I-C locus lacks an array component essential for assembling an interference complex. Thus, the reason for sustaining the expense of a cluster of cas genes (I-C) is obscure. Type I-C (previously Dvulg) is the only CRISPR subtype that engages Cas5c, a Cas5 variant, to process precursor CRISPR-RNA (pre-crRNA). In this study, thus, the recombinant Cas5c (rLinCas5c) of L.interrogans and its mutant variants were cloned, expressed, and purified. The purified rLinCas5c is illustrated as metal-independent, sequence, and size-specific cleavage on repeat RNA and pre-crRNA of subtype I-B or orphan CRISPR array. However, the Cas6-bound mature crRNA of subtype I-B fends off from the rLinCas5c activity. In addition, rLinCas5c holds metal and size-dependent DNase activity. The bioinformatics analysis of LinCas5c inferred that it belongs to the subgroup Cas5c-B. Substitution of Phe141 with a more conserved His residue and deletion of unique (β1'-β2') insertions usher a gain of rLinCas5c activity over nucleic acid. Overall, our results uncover the functional diversity of Cas5c ribonucleases and infer an incognito auxiliary role in the absence of a cognate CRISPR array.Leptospira interrogans serovar Copenhageni's genome harbors two CRISPR-Cas systems belonging to subtypes I-B and I-C. However, in L. interrogans, the subtype I-C locus lacks an array component essential for assembling an interference complex. Thus, the reason for sustaining the expense of a cluster of cas genes (I-C) is obscure. Type I-C (previously Dvulg) is the only CRISPR subtype that engages Cas5c, a Cas5 variant, to process precursor CRISPR-RNA (pre-crRNA). In this study, thus, the recombinant Cas5c (rLinCas5c) of L.interrogans and its mutant variants were cloned, expressed, and purified. The purified rLinCas5c is illustrated as metal-independent, sequence, and size-specific cleavage on repeat RNA and pre-crRNA of subtype I-B or orphan CRISPR array. However, the Cas6-bound mature crRNA of subtype I-B fends off from the rLinCas5c activity. In addition, rLinCas5c holds metal and size-dependent DNase activity. The bioinformatics analysis of LinCas5c inferred that it belongs to the subgroup Cas5c-B. Substitution of Phe141 with a more conserved His residue and deletion of unique (β1'-β2') insertions usher a gain of rLinCas5c activity over nucleic acid. Overall, our results uncover the functional diversity of Cas5c ribonucleases and infer an incognito auxiliary role in the absence of a cognate CRISPR array.